Biopsychosocial Determinants of Adolescent Mental Health and Risk Behaviors: A Convergent Cross-Sectional Mixed-Methods Study in West Java, Indonesia - Yuliani, Indah; Aisyah, Aisyah; Nur’aliyah, Anisa; Herwansah, Diki; Salam, Ikeu Anggita; Gopur, Gopur (Journal of Applied Nursing and Health, 2026)
Background: Adolescent mental health disorders are an increasing public health concern in Indonesia. Although precision nursing offers a personalized approach, evidence integrating biopsychosocial, healthcare access, and cognitive-literacy factors across diverse healthcare settings remains limited. This convergent mixed-methods study aimed to identify determinants of adolescent mental health outcomes and risk behaviors while exploring how adolescents’ lived experiences complement quantitative findings to inform precision nursing interventions. Methods: A convergent cross-sectional mixed-methods study was conducted, reported in accordance with the Good Reporting of A Mixed Methods Study (GRAMMS) guideline, with 140 adolescents (aged 12–21 years) recruited across four healthcare settings in West Java, Indonesia Primary Healthcare Centers, hospital outpatient clinics, primary clinics, and community health centers (including both hospital and primary healthcare facility types). Participants were selected using proportional purposive sampling for the quantitative strand, and a purposively selected subsample (n=20) drawn from quantitative respondents was recruited for semi-structured qualitative interviews until thematic saturation was reached. Inclusion criteria were adolescents aged 12–21 years attending participating facilities who provided informed consent. Exclusion criteria included acute psychiatric crisis and severe cognitive impairment. Validated instruments included the Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), WHO-5 Wellbeing Index, Perceived Stress Scale-10 (PSS-10), and Columbia Suicidality Severity Rating Scale (C-SSRS). Social, family support, healthcare access, and cognitive-literacy factors were assessed using structured questionnaires. Qualitative data were gathered through semi-structured interviews (n=20) and analyzed using inductive thematic analysis; quantitative and qualitative findings were integrated through a joint display comparing statistical results with interview themes to assess convergence and complementarity. Ethical approval was obtained from the STIKes Abdi Nusantara Ethics Committee. Data were analyzed using descriptive statistics, chi-square, and Spearman correlation with IBM SPSS Statistics Version 26. Results: Among 140 adolescents (mean age 17.2 ± 2.1 years; 54.3% male), 82.1% reported at least mild depressive symptoms (PHQ-9 ≥5), with 7.9% in the severe range. Anxiety symptoms (GAD-7 ≥5) were present in 77.9% of participants. Non-suicidal self-injury (NSSI) was reported by 14.3% (n=20). Family history of mental disorder was significantly associated with higher PHQ-9 scores (p=0.008). Low family support was present in 22.9% and correlated with greater depression severity (r=0.42, p<0.001). Poor cognitive function and health literacy were associated with higher risk behavior scores (r=0.41, p<0.01). Adolescents utilizing hospital services had significantly higher depression and anxiety scores compared to Primary Healthcare Center users (p<0.05). Three qualitative themes emerged from the interviews: (1) academic pressure and emotional burden, (2) family communication barriers, and (3) limited access to adolescent-friendly mental health services. These themes complemented and explained the quantitative findings, clarifying why low family support and poor health literacy were associated with worse mental health outcomes Conclusion: Depressive and anxiety symptoms are highly prevalent among adolescents across all healthcare settings in West Java. Family support, cognitive function, health literacy, and healthcare access are significant determinants of mental health outcomes. Integrating quantitative and qualitative findings demonstrates that family-centered and health literacy-based precision nursing interventions should be prioritized across Indonesian healthcare settings. These findings support the development of precision nursing interventions tailored to the multi-determinant profile of adolescent mental health. At the same time, future longitudinal mixed-methods studies are needed to validate these findings.